Wartości społeczno-moralne w czasopiśmie "Ateneum Kapłańskie" (na przykładzie artykułów ks. Stefana Wyszyńskiego z lat 1932-1939) = Socio-moral values in the journal "Ateneum Priest" (on the example of the articles of Fr Stefan Wyszynski from 1932-1939) - Baron, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the introduction, I am introducing the silhouette of Fr. Stefan Wyszyński. I read the magazine "Ateneum Priest", in which in 1932-1939 Fr. Wyszyński served as editor-in-chief.I specify and justify the choice of research area. I set the basic purpose of the work, whichis to determine what social-moral values he was trying to, and which antidotes ks. StefanWyszyński stigmatized.
Keywords: wartości społeczno-moralne; wychowanie; młodzież; rodzina; warstwa chłopska; bezrobocie; socio-moral values; youth education; family; peasantry; unemployment